The ablation of plastics by intense pulsed ion beam - Yu, Xiao; Zhang, Shijian; Zhang, Nan; Zhong, Haowen; Liang, Guoying; Xu, Mofei; Kuang, Shicheng; Ren, Jianhui; Shang, Xuying; Yan, Sha; Remnev, Gennady Efimovich; Le, Xiaoyun (Surface & coatings technology, 2020)
With strong flash heating effects, intense pulsed ion beam (IPIB) may induce ablation on the solid surface and it is the basis of applications such as surface cleaning, nanopowder preparation and thin-film synthesis with IPIB. In this study, the ablation of polymethyl methacrylate (PMMA) by IPIB was investigated with varied beam energy density on pulsed ion beam accelerator BIPPAB-450 to study the ablation of IPIB under strong ablation. With thermal imaging measurement, it is revealed that when energy reaches a certain threshold, the ablation plume generated on the target surface may impose a shielding effect on the ion beam energy from depositing in the target. It is verified by thermal field simulation that for the low evaporation temperature and high thermal resistance, intense ablation plume may be generated on the surface of plastics under low IPIB energy density or at the early stage of IPIB irradiation. Ablation mass measurement demonstrated that under irradiation of IPIB with a pulse length of 120 ns, ion energy up to 450 keV, energy density up to 3.8 J/cm2, the mass loss of the target increases with the rise of IPIB energy density. Under the irradiation of a series of pulses, the mass loss of PMMA increases proportionally. Unlike ablation on metals by direct beam energy deposition, the ablation of plastics by IPIB endures more stages and the ablation may be more achieved by the heated ablation plasma by beam irradiation. •Beam energy shielding effects under strong ablation by pulsed ion beam•Ablated plasma indirect ablation to the substrate under beam irradiation•Proportional mass loss with pulse number under strong ablation